DYNAMICS AND CONTROL OF BRUCELLOSIS IN HUMAN AND LIVESTOCK: PUBLIC HEALTH EDUCATION, TREATMENT AND VACCINATION - Abdullahi, Mohammed Baba; Sule, Amiru (FUDMA Journal of Sciences, 2023)
Brucellosis is a multifaceted zoonotic infection with vital epidemiological, economic, and global health effect, principally for human and Livestock populations within developing nations. In this paper a dynamic model of livestock-to-human transmission of the disease is developed. Model investigation is carried out to obtain and establish the stability of the equilibrium points. The basic reproduction number is calculated and the conditions under which brucellosis can be cleared in the both populations are established. Then, optimal control approach to establish the required conditions for the optimality of the disease eradication or control are applied. Public health education for humans and vaccination for susceptible livestock and treatment for infected humans and livestock. Numerical simulations show the dynamics of disease transmission and the effect of the control strategies.
Keywords: Dynamics; Control; Brucellosis; Livestock; Public Health Education; Treatment; Vaccination